Strength in numbers in index insurance - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
On 20-22 January, 2014, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and the CGIAR Research Program on Policies, Institutions, and Markets (PIM) hosted a workshop on Mobilizing a CGIAR Agricultural Insurance Research Community. The workshop took place at the International Food Policy Research Institute (IFPRI) in Washington, DC. Andrew Mude of the International Livestock Research Institute and Maximo Torero, IFPRI spoke about new opportunities for collaboration in index insurance research and implementation. Read more about CCAFS work on index insurance: https://ccafs.cgiar.org/weather-index-based-insurance